2021
DOI: 10.3389/fvets.2021.655311
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Endocannabinoids as Diagnostic Markers of Canine Chronic Enteropathies: A Pilot Study

Abstract: Chronic enteropathies (CEs) in dogs, according to the treatment response to consecutive trials, are classified as food-responsive (FRE), antibiotic-responsive (ARE), and immunosuppressive-responsive (IRE) enteropathy. In addition to this classification, dogs with loss of protein across the gut are grouped as protein-losing enteropathy (PLE). At present, the diagnosis of CEs is time-consuming, costly and sometimes invasive, also because non-invasive biomarkers with high sensitivity and specificity are not yet a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
0
3
1
Order By: Relevance
“…Masoodi et al found that there was no significant relationship between OEA levels and age in their control population or the CLL population; however, it is important to note the majority of their CLL patients were older with 97% being above 50 years and 80% above 60 years old (15). Our results contrast a study on canine chronic enteropathy by Febo et al in which there was no significant association between endocannabinoids and age in healthy dogs (33). This may have been influenced by the age of the control group, the median age of our control group was 84 months as compared to 60 months in their population, however further research evaluating the impact of age is needed.…”
Section: Discussioncontrasting
confidence: 91%
“…Masoodi et al found that there was no significant relationship between OEA levels and age in their control population or the CLL population; however, it is important to note the majority of their CLL patients were older with 97% being above 50 years and 80% above 60 years old (15). Our results contrast a study on canine chronic enteropathy by Febo et al in which there was no significant association between endocannabinoids and age in healthy dogs (33). This may have been influenced by the age of the control group, the median age of our control group was 84 months as compared to 60 months in their population, however further research evaluating the impact of age is needed.…”
Section: Discussioncontrasting
confidence: 91%
“…In the current study, the PROT_LoCHO group showed decreased levels of the O-acylglycerol endocannabinoid substrates of the ABDH12 lipase relative to HiCHO, perhaps indicating a role for this food in mitigating adverse effects of obesity on skeletal muscle. The O-acylglycerol endocannabinoid 2-arachidonoylglycerol is increased in circulation of dogs with chronic gastroenteritis relative to healthy dogs [ 95 ] and in the synovial fluid of dogs with osteoarthritis [ 96 ]. In the current study, 2-arachidonoylglycerol decreased following consumption of both LoCHO foods relative to HiCHO, perhaps offering an opportunity for dietary carbohydrate replacement by protein or fat to ameliorate chronic inflammatory conditions in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Palmitic acid was implicated in the pathogenesis of human IBD [46], and its role in intestinal health has been discussed, this fatty acid having been implicated as a ligand of Toll-like receptors (TLR4) [47], whereas down-or upregulation of TLR expressions are found in different canine CE conditions [48,49]. It is also important at this point to consider that membrane phospholipid composition also influences the balance of lipid mediators involved in intestinal diseases; therefore, mediators from palmitic acid, such as palmitoylethanolamide [50,51] and, from PUFA, for example, docosahexanoyl serotonin [52], can be influenced by the change in the precursor's levels in the membrane.…”
Section: Discussionmentioning
confidence: 99%